ANALISIS COUNTER TERRORISM OLEH PEMERINTAH NIGERIA DALAM MENANGANI KELOMPOK BOKO HARAM - Dwi Rizki Woelandari; Rachma Putri; Rezky Apriliantini; Helen Hii; Nasranita Novelin Papuani Tebai (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2021)
This paper is aims to analyze counter terrorism efforts carried out by the Nigerian government internally and externally in dealing with the actions of the Boko Haram terrorist group which caused losses, fear and anxiety for the citizens of Nigeria and the government of Nigeria. The Boko Haram terrorist group can thrive to this day in Nigeria due to several factors including an unstable government, ideological differences, social and economic inequalities. In this case, the author uses the theory of counter terrorism which explains that the handling of acts of terrorism in a country can be carried out in three ways, namely prevention, protection and response through Nigeria's internal and external efforts. The research method used a descriptive research method with a qualitative approach. In collecting data, the author used literature study to find and browse information from literature books, research journals and from news websites related to the research problems discussed. The finding of this study indicates that the efforts made by the Nigerian government internally and externally through counter terrorism in dealing with the Boko Haram terrorist group to date have their respective strengths and weaknesses. And these two efforts must be carried out in a balanced way in order to effectively eradicate the terrorist acts of Boko Haram. Keywords: Counter Terrorism; Nigerian Goverment; Boko Haram.